How beneficial is the use of probiotic supplements for the aging gut?. (April 2011) - Cusack, Siobháán; Claesson, Marcus J; O''Toole, Paul W
The specific health benefits of probiotic supplementation in aging populations remain relatively undefined. Although some probiotic research performed to date has focused on specific populations –– particular disease groups or those in dynamic life stages such as the very young and older adults –– dedicated studies of older subjects with a typical range of age-related conditions are few. Published studies also feature a narrow range of probiotic strains. Exploitation of strain specificity to modulate the composition and function of the microbiota is crucial to maximize the potential benefit of probiotics. A combination of prebiotic (dietary) and probiotic agents may prove most effective in targeted modulation of the microbiota. The efficacy of specific probiotic strains in modulating the microbiota of older populations is worth pursuing, although the role of antibiotics and polypharmacy (use of multiple medications) in influencing the potential benefits of probiotic intervention requires more dedicated study.